Otolith Growth Rings Pattern of Pangasius polyuranodon Bleeker, 1852 from the Sail River and Kampar Kiri River, Riau Province - Fitrah A. Tamba; Windarti Windarti; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract The Sail  River and Kampar Kiri River have different ecosystems characteristic and it may be reflected in the otolith’s growth ring patterns in the otolith of fish living in those areas. A research aims to understand the growth pattern present in the otolith of Pangasius polyuranodon. The fish were caught using nets and bamboo trap, once/week. There were 119 fishes (50 fishes from the River Sail and 69 fishes from Kampar Kiri River). The otoliths (sagita) were removed and processed following Windarti (2017). Growth  rings pattern was studied using a binocular microscope. The otolith in the Sail River length was 1- 2.175 mm and their weight was 0.0019-0.0075 mg. Whereas in the  Kampar Kiri River  length was 2-3.25  mm andtheir weight 0.0030-0.0267 mg. The  distance between the nucleus and the first dark ring was varied  from the Sail River (0.02-0.75mm) and Kampar Kiri River (0.025-0.75 mm). Results shown that the maximum number of dark ring in the otolith of fish living in the Sail River was 3, while that of the fish from the Kampar Kiri River was 4. Water quality in the sampling area was good and it may be suffcient to support  the life of Pangasius polyuranodon.   Keywords: Dark Ring, Otolith, Growth Pattern, Sagita